Anthocyanin accumulation in juvenile Schima superba leaves is a growth trade-off by consuming energy for adaptation to high light during summer. (22nd October 2018) - Yu, Zhengchao; Zhang, Qilei; Zheng, Xiaoting; Huang, Xuandong; Peng, Changlian
Abstract: Aims: Anthocyanin accumulation is the main factor underlying why young plant leaves turn red, and plant growth follows the principle of maximizing the economic efficiency of energy. There is a need to verify the role of young plant leaves turning red and confirm whether anthocyanin accumulation overconsumes the energy of the plant. Methods: We compared the different pigment contents, antioxidant capacities, leaf mass per area, photosynthetic characteristics, dark respiration rates, light compensation points (LCPs) and electron flow distribution of young and mature Schima superba leaves grown under full sunlight and 30% full sunlight conditions. We then examined the correlations between anthocyanins and total antioxidant capacity, photosynthetic pigments, dark respiration rates, LCPs by using linear regression. Finally, we analyzed Pearson correlation coefficients and used principal component analysis to evaluate the interactions of these functional indicators. Important Findings: The young leaves of S. superba accumulated anthocyanins in full sunlight but not in 30% full sunlight. Anthocyanins substantially contributed to the total antioxidant capacity (accounting for 33.29%) in juvenile S. superba leaves. Young leaves containing more anthocyanin accumulated less reactive oxygen species after high light (HL) treatment. However, juvenile leaves accumulating anthocyanins showed 56.97% higher dark respiration rates, 24.79% higher LCPs and 5.32% higher allocations of electron flow to photorespiration and lower organic substance accumulation than did those without anthocyanins. These results suggest that young S. superba leaves must consume more energy to accumulate anthocyanins to adapt to HL environments. Therefore, plants sacrifice growth rate to ensure survival, which is a trade-off for their ability to respond to external environments.